The Effect of E-WOM, Brand Awareness and Prices on Interest in Buying Mama Perfum Products in Bandar Labuhan Village, Tanjung Morawa District Deli Serdang Regency - Aina Anjani; Adrial Falahi (International Journal of Economics (IJEC), 2022)
This study aims to determine the effect of E-WOM, brand awareness and price on interest in buying Mama Parfum products in Bandar Labuhan Village, Tanjung Morawa District, Deli Serdang Regency. The data analysis method used in this research is descriptive and quantitative. This research was conducted in Bandar Labuhan Village, Tanjung Morawa District, Deli Serdang Regency. The population in this study was the people of Bandar Labuhan Village with the age criteria of 16 - 56 years with a total of 2,166 men, 2,484 women and a total of 4,650 people with a tolerance limit of 10% which was calculated by the slovin rule, the total sample size was 98. respondents with a sampling technique using the simple random sampling . Data collection techniques using observation, interviews and questionnaires. The results of the multiple linear regression test obtained the equation Y = 0.486 + 0.40 7 X1 + 0.460X2 + 0.218X3 , meaning that the variables E-WOM, brand awareness and price have a positive effect on buying interest. The results of the coefficient of determination (R2 ) show that R is 0.857, R Square ( R2 ) is 0.726, Adjusted R Square is 0.726 or 72.6%, while the remaining 27.4% is explained by other variables not included in this study